Suicide among young people in selected Brazilian State capitals - Edinilsa Ramos de Souza; Maria Cecília de Souza Minayo; Juaci Vitória Malaquias
This study analyzes suicide among young Brazilians (15-24 years old) in nine metropolitan areas. Mortality data for 1979-1998 were obtained from the Mortality Information System of the Ministry of Health. External causes are the main causes of death among youth, and suicide is the sixth most frequent of these causes. The distribution is heterogeneous, varying according to the social stratum, specific age group, sex, and means used to commit suicide. All cities analyzed showed increased suicide rates from 1979 to 1998 (from 3.5 to 5.0 per 100,000 inhabitants 15-24 years old). Salvador and Rio de Janeiro had the lowest suicide rates, while Porto Alegre and Curitiba had the highest. The principal means used by youth to commit suicide were hanging, strangling, and suffocation (Porto Alegre), followed by firearms and explosives (Belo Horizonte).